IMPACTS OF HISTORICAL LAND USE CHANGES ON EROSION AND AGRICULTURAL SOIL PROPERTIES IN THE KALI BASIN AT LAKE BALATON, HUNGARY - Szilassi P.; Jordan G.; Csillag G.; van Rompaey A. (My University, 2006)
Historical land use changes may have significant impact on erosion and agricultural soil properties, including soil degradation by acidification, nutrient leaching and organic matter depletion. The Kali Basin study area, a small catchment of high landscape value located in a national park at Lake Balaton, Hungary, with its historical agricultural records, together with the available unique historical land use data for the last 200 years, provides an opportunity to study and model impacts of historical land use changes on erosion and agricultural soil properties. Comparison of long-term land uses with present soil degradation indicator parameters showed that permanent arable land use has led to degradation of both the physical and chemical properties of soils in the Kali Basin. Application of the SEDEM/WATEM distributed erosion and sediment transport model showed that, despite the low overall sediment export from the catchment, land use changes introduced by property ownership and agricultural changes have decreased average soil erosion in the catchment but increased relative sediment export to Lake Balaton. This is due to changes in the land cover pattern that allow more sediment transported to the river system. The overall conclusion of this study is that besides the size and area proportion of land use types, land use pattern seems to be equally important in soil erosion and degradation processes, thus land use pattern is a key factor for landscape planning and development in the Kali Basin. A relationship between the sociological and agro-ecological reasons for the recorded land use changes is also shown in this study. © 2006 Elsevier B.V. All rights reserved.
Keywords: AGRICULTURE; CATCHMENT; EROSION MODEL; GIS; LAND USE CHANGE; SOIL